2009
DOI: 10.1111/j.1365-2923.2008.03278.x
|View full text |Cite
|
Sign up to set email alerts
|

Medical students’ perceptions of identity in communication skills training: a qualitative study

Abstract: Students' perceptions challenge educational goals, suggesting that there is limited potential for the formation of professional identity through early training. Teacher-doctors must acknowledge how students' low levels of clinical competence and patients' behaviour complicate students' identity formation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
0
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 11 publications
(17 reference statements)
1
24
0
2
Order By: Relevance
“…A recent study revealed that some first year students had difficulty communicating with patients because they did not have sufficient skills and medical knowledge, and that the students "enacted other identities", leading to poor communication. 35 One conclusion drawn from this study was that educators need to take into account the ways that low levels of knowledge in the early years of medical training can make the development of professional identity much more complex and difficult. 35 Interactions with other healthcare professionals as well as patients play a crucial role in the professional identity formation of student doctors.…”
Section: (P49)mentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study revealed that some first year students had difficulty communicating with patients because they did not have sufficient skills and medical knowledge, and that the students "enacted other identities", leading to poor communication. 35 One conclusion drawn from this study was that educators need to take into account the ways that low levels of knowledge in the early years of medical training can make the development of professional identity much more complex and difficult. 35 Interactions with other healthcare professionals as well as patients play a crucial role in the professional identity formation of student doctors.…”
Section: (P49)mentioning
confidence: 99%
“…35 One conclusion drawn from this study was that educators need to take into account the ways that low levels of knowledge in the early years of medical training can make the development of professional identity much more complex and difficult. 35 Interactions with other healthcare professionals as well as patients play a crucial role in the professional identity formation of student doctors. For example, the morning report where students directly interact with more senior doctors, is a locus for deploying discourses that shape professional identity by emphasising scientific and downplaying humanistic approaches as well as for reinforcing existing systemic hierarchies.…”
Section: (P49)mentioning
confidence: 99%
“…The role of the learning environment has been highlighted, 19 and Phillips et al 20 Additional PIF literature in medicine highlights the importance of experiential learning, early clinical experiences, role models, discourse, socialization, and relationships. [25][26][27][28] Students' level of developing expertise may also impact PIF, 29 as reflected in their understanding and approach to professional dilemmas. 30 The literature further underscores the importance of self-reflection in identity development.…”
Section: Introductionmentioning
confidence: 99%
“…A literatura [10][11][12][13][14][15][16] atesta tal afirmação, demonstrando que, nas escolas médicas, a construção da postura ética e o pensamento crítico e reflexivo se desenvolvem a partir de disciplinas e condutas que se aprendem nas salas de aula, nos laboratórios e, principalmente, observando os professores em ação na práti-ca cotidiana. Ao mesmo tempo em que afirmam que os alunos, pela observação dos mestres, "modelam" comportamentos e, assim, de certa forma, constroem uma identidade médica, tais estudos contrariam a suposição de que os alunos, por serem adultos com personalidades já formadas, não modificariam valores e atitudes mediante aprendizado na escola médica.…”
Section: Introductionunclassified